Analysis of the level of compliance with tax obligations, in the taxpayers of a shopping center, Arequipa-Peru during the year 2022 (Dimensión Empresarial, 2024)
The present article analyzes the level of compliance with Tax Obligations, by the taxpayers of a shopping center in Arequipa in Peru, 2022. Type of descriptive research, with a non-experimental design. The sample of 45 taxpayers of the FECETRAM NRUS. Instrument the questionnaire; the results showed that the level of compliance with tax obligations is medium with 53%, it is low at 42%, and high at 4%, for formal tax obligations it shows a low level of compliance at 44%, medium level 42% and, on the other hand, with a high level 13%; at the same time, for substantial tax obligations it is low at 49%, medium at 44% and high at 7%.
Keywords: Tax obligation; Substantial tax obligations; Formal tax obligations; Microentrepreneurs